Assessing the yield difference of double-cropping rice in South China driven by radiation use efficiency - Jian Lu; Sicheng Deng; Muhammad Imran; Jingyin Xie; Yuanyuan Li; Jianying Qi; Shenggang Pan; Xiangru Tang; Meiyang Duan (Journal of Integrative Agriculture, 2024)
Double-cropping rice in South China continues to break the total yield record, but the yield potential of single-cropping rice is not being realized. Radiation use efficiency (RUE) has been singled out as an important determinant of grain yield in many cereal species. However, there is no information on whether the yield gaps in double-cropping rice involve differences in RUE. Field experiments were performed over two years to evaluate the effects of intercepted radiation (IP) and RUE on the above-ground biomass production, crop growth rate (CGR), and harvest index (HI), in four representative rice varieties, i.e., Xiangyaxiangzhan (XYXZ), Meixiangzhan 2 (MXZ2), Nanjingxiangzhan (NJXZ), and Ruanhuayoujinsi (RHYJS), during the early and late seasons of rice cultivation in South China. The results revealed that grain yield in the early season was 8.2% higher than in the late season. The yield advantage in the early season was primarily due to higher spikelets per panicle and above-ground biomass resulting from a higher RUE. The spikelets per panicle in the early season were 6.5, 8.3, 6.9, and 8.5% higher in XYXZ, MXZ2, NJXZ, and RHYJS, respectively, than in the late season. The higher early season grain yield was more closely related to RUE in the middle tillering stage (R2=0.34), panicle initiation (R2=0.16), and maturation stage (R2=0.28), and the intercepted photosynthetically active radiation (IPAR) in the maturation stage (R2=0.28), while the late season grain yield was more dependent on IPAR in the middle tillering stage (R2=0.31) and IPAR at panicle initiation (R2=0.23). The results of this study conclusively show that higher RUE contributes to the yield progress of early season rice, while the yield improvement of late season rice is attributed to higher radiation during the early reproductive stage. Rationally allocating the RUE of double-cropping rice with high RUE varieties or adjustments of the sowing period merits further study.